Calculation of Value Added Tax as A Tax Obligation for Taxable Entrepreneurs - Maria Lapriska Dian Ela Revita; Dian Berliansyah Putra; Heri Aryadi; Natal Indra (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The economic activities that we carry out on a daily basis, consciously or unconsciously, actually come into direct contact with taxes, namely VAT (Value Added Tax). VAT is a levy imposed on a sale and purchase transaction of Taxable Goods/Services conducted by a Taxable Entrepreneur (PKP). PKP can be subject to sanctions in the form of administration such as fines and/or interest to criminal sanctions if they are late in making tax invoices and reporting periodic tax returns. Calculation of VAT Value, which includes Input VAT and Output VAT is carried out, to determine Underpaid VAT or Overpaid VAT on the Periodic Tax Return Report. The purpose of the research is to find out how the mechanism for collecting and calculating VAT obligations for PKP, and calculating the value of PKP Input and Output VAT. At this writing the writer uses descriptive qualitative methods and literature studies. Output tax is the same as sales transactions, input taxes are the same as purchase transactions. Input Tax in a Tax Period is credited with Output Tax in the same Tax Period, in accordance with statutory provisions. Credited Input Tax must use a Tax Invoice. Tax Invoice is proof of tax collection made by a Taxable Entrepreneur who delivers Taxable Goods or delivers Taxable Services. If the output tax is greater (>) than the input tax, then the PKP pays VAT to the state treasury. The output tax is less (<) than the tax, so the excess VAT is compensated for the next tax period. Credited Input Tax must use a Tax Invoice. Tax Invoice is proof of tax collection made by a Taxable Entrepreneur who delivers Taxable Goods or delivers Taxable Services. If the output tax is greater (>) than the input tax, then the PKP pays VAT to the state treasury. The output tax is less (<) than the tax, so the excess VAT is compensated for the next tax period.